The Career Transitioning Experiences of Nigerian Economic Immigrants in Canada: Reliance on Christian Faith and Personal Agency - Adekoya, Ibukunoluwa; Sinacore, Ada L. (Canadian Journal of Counselling and Psychotherapy, 2022)
Career transitioning among immigrants in Canada is a widely studied phenomenon. However, little research exists on the experiences of sub-Saharan African immigrants. In Canada, immigrants from African countries represent a significant proportion of the immigrant labour force, yet they experience the highest unemployment rates compared to their counterparts from all other continents in the world (Yssaad & Fields, 2018). The current study used phenomenology as a methodology and intersectionality as an epistemology to explore the challenges and coping strategies of six Christian Nigerian economic immigrant (NEI) women and men undergoing career transitioning in Canada. Results revealed the salience of career transitioning in the socio-cultural, occupational, and socio-economic aspects of NEIs’ lives. Their Christian faith and personal agency were interconnected sources of strength for overcoming transitioning challenges. Implications for counselling and further research are discussed.